2015
DOI: 10.1111/febs.13211
|View full text |Cite
|
Sign up to set email alerts
|

How pyridoxal 5′‐phosphate differentially regulates human cytosolic and mitochondrial serine hydroxymethyltransferase oligomeric state

Abstract: Adaptive metabolic reprogramming gives cancer cells a proliferative advantage. Tumour cells extensively use glycolysis to sustain anabolism and produce serine, which not only refuels the one-carbon units necessary for the synthesis of nucleotide precursors and for DNA methylation, but also affects the cellular redox homeostasis. Given its central role in serine metabolism, serine hydroxymethyltransferase (SHMT), a pyridoxal 5 0 -phosphate (PLP)-dependent enzyme, is an attractive target for tumour chemotherapy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
107
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 70 publications
(114 reference statements)
13
107
0
3
Order By: Relevance
“…In general, most of SHMT2 proteins form homodimer in cells without enzymatic activity (2). To activate its activity, SHMT2 goes through a transformation process to form tetramers after binding PLP at the K280 site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, most of SHMT2 proteins form homodimer in cells without enzymatic activity (2). To activate its activity, SHMT2 goes through a transformation process to form tetramers after binding PLP at the K280 site.…”
Section: Discussionmentioning
confidence: 99%
“…As most of SHMT2 proteins form homodimers in cells without enzymatic activity, they must form tetramers to become active forms (2). Therefore, we further investigated whether K280E, which lowered the enzymatic activity of SHMT2 (Fig.…”
Section: K280 Is the Major Succinylation Site Of Shmt2mentioning
confidence: 99%
See 1 more Smart Citation
“…The results reveal that apo and holo-hOAT exhibit similar tertiary structure, as shown by their near-UV CD spectra. Changes of the dichroic bands in the near-UV region during the apo to holo transition in Fold Type I aminotransferases were previously associated with changes in the position/orientation of aromatic residues at or in proximity of the active site [33]. In this family, PLP coordination typically involves a planar π base stacking interaction between the PLP pyridine ring and a tryptophan indolic ring, along with an H-bond interaction between a tyrosine residue belonging to the neighboring subunit and the phosphate group of PLP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, at present, it is not easy to understand how PLP binding can impact the tetrameric structure of the enzyme. In this regard, a conformational change has been associated to the PLP-induced tetramerization of mitochondrial human serine hydroxymethyltransferase [33]. The authors have suggested that PLP binding to the apoform shifts the equilibrium from an “open” to a “close” conformation of the dimers promoting the tetramerization.…”
Section: Discussionmentioning
confidence: 99%